KOMUNIKASI DALAM PERSPEKTIF IMPERIALISME KEBUDAYAAN - Heldi Yunan Ardian (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2018)
Globalization  has  removed  the  boundaries  of  communication  systems  between  one  region  and  another  region that is transferred very fast through various media such as television, magazines, and internet. National culture in  a  country  is  rapidly  becoming  a  global  culture  and  becoming  a  capable  industry  in  influencing  national culture  in  other  countries.  Cultural  In  the  era  of  reform,  imperialism  appears  to  be  more  prominent  than  the previous regime era that influenced all the  joints  of economic, political and cultural  life.  Cultural  imperialism today,  not  only  from  the  West  but  also  from  non-Westerners  like  India,  Korea,  China,  Japan  and  Turkey.  In response  to  this,  an  open  cultural  strategy  is  needed  to  take  the  universal  values  in  all  areas  of  science, technology, economics and culture without losing the identity as a sovereign and dignified nation in the midst of other nations. Traditional culture is a valuable national treasure and does not bother the process of development and modernization.Keywords:  globalization, imperialism, identity